Preparation and reactions of 4-iodobutyl pinacolborate. Synthesis of substituted alkyl and aryl pinacolboronates via 4-iodobutyl pinacolborate utilizing tetrahydrofuran as the leaving group. Issue 23 (3rd June 2015) - Murphy, Chris L.; Hall, Aaron; Roberts, Emily J.; Ryan, Matthew D.; Clary, Jacob W.; Singaram, Bakthan
Graphical abstract: Abstract: Iodine reacts with 4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolane (HBpin), under ambient reaction conditions in THF, to form the iodoalkylborate species 2-(4-iodobutoxy)-4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolane (4-IboxBpin). Apparently, one-half equivalent of I2 reacts with HBpin to form IBpin in pentanes, which in turn cleaves THF to form the 4-IboxBpin. Alkyl and aryl Grignard reagents, prepared under Barbier conditions, then react with 4-IboxBpin to form the corresponding alkyl and aryl pinacolboronates while reforming and liberating THF as the leaving group.